Endometriosis-related infertility in China: analysis of the global burden of disease study 2021 - Lao, Jianting; Shen, Dongyi; Hu, Panwei; Song, Yanhua; Yang, Hong (Frontiers in Public Health, 2025)
ObjectiveUtilizing the Global Burden of Disease (GBD) 2021 dataset, this study analyzed temporal trends (1990–2021) and age-period-cohort patterns of endometriosis-related infertility burden in China versus globally. By employing joinpoint regression and APC modeling, we aimed to identify key epidemiological shifts and disparities, thereby providing evidence-based insights for optimizing health service planning and resource allocation strategies targeting endometriosis-related infertility.MethodsUsing age-standardized prevalence rates (ASPR) of endometriosis-related infertility (1990–2021) from the GBD 2021 database, we analyzed Chinese females aged 15–49 years. Joinpoint regression identified significant trend changes in ASPR, while age-period-cohort (APC) modeling decomposed effects into age, period, and birth cohort dimensions using 5-year intervals.ResultsIn 2021, the age-standardized prevalence rate (ASPR) of patients with endometriosis-related primary infertility in China was 280.63 per 100,000 population (95% UI: 115.61 to 616.39). The percentage change in ASPR for endometriosis-associated primary infertility in China between 1990 and 2021 was −23.35% (95% UI: −10.52% to −32.68%) above the global level −29.61% (95% UI: −37.19% to −24.79%). In 2021, the ASPR of patients with endometriosis-associated secondary infertility in China was 1849.35 per 100,000 population (95% UI: 1104.61 to 2931.00). The percentage change of endometriosis-associated secondary between 1990 and 2021 ASPR in China was −38.16% (95% UI: −43.81% to −31.53%), below the global level −24.70% (95% UI: −27.99% to −21.11%).ConclusionThe ASPR of endometriosis-related female infertility in China and globally declined between 1990 and 2021. This indicates that China has attained significant progress in addressing and managing endometriosis-related female infertility. However, the overall burden of endometriosis-related female infertility remains substantial and requires continued attention.